At Westonci.ca, we provide reliable answers to your questions from a community of experts. Start exploring today! Experience the ease of finding reliable answers to your questions from a vast community of knowledgeable experts. Connect with a community of professionals ready to provide precise solutions to your questions quickly and accurately.
Sagot :
To find the solutions for the quadratic equation [tex]\(3x^2 + 8x + 4 = 0\)[/tex], we need to determine the roots of the equation. This is typically done using the quadratic formula:
[tex]\[ x = \frac{-b \pm \sqrt{b^2 - 4ac}}{2a} \][/tex]
where [tex]\(a\)[/tex], [tex]\(b\)[/tex], and [tex]\(c\)[/tex] are the coefficients of the terms in the quadratic equation [tex]\(ax^2 + bx + c = 0\)[/tex]. For our specific equation [tex]\(3x^2 + 8x + 4 = 0\)[/tex], the coefficients are:
- [tex]\(a = 3\)[/tex]
- [tex]\(b = 8\)[/tex]
- [tex]\(c = 4\)[/tex]
Given the values of [tex]\(a\)[/tex], [tex]\(b\)[/tex], and [tex]\(c\)[/tex], we substitute them into the quadratic formula to solve for [tex]\(x\)[/tex]:
1. Compute the discriminant: [tex]\(b^2 - 4ac\)[/tex]
[tex]\[ b^2 - 4ac = 8^2 - 4 \cdot 3 \cdot 4 = 64 - 48 = 16 \][/tex]
2. Compute the two roots using the quadratic formula:
[tex]\[ x_1 = \frac{-b + \sqrt{b^2 - 4ac}}{2a} = \frac{-8 + \sqrt{16}}{2 \cdot 3} = \frac{-8 + 4}{6} = \frac{-4}{6} = -\frac{2}{3} \][/tex]
[tex]\[ x_2 = \frac{-b - \sqrt{b^2 - 4ac}}{2a} = \frac{-8 - \sqrt{16}}{2 \cdot 3} = \frac{-8 - 4}{6} = \frac{-12}{6} = -2 \][/tex]
These calculations yield the roots of the quadratic equation. Therefore, the solution set for the equation [tex]\(3x^2 + 8x + 4 = 0\)[/tex] is:
[tex]\[ \boxed{-\frac{2}{3}, -2} \][/tex]
In decimal form, these roots are approximately:
[tex]\[ \boxed{-0.66666667, -2} \][/tex]
Hence, the values which satisfy the given quadratic equation are [tex]\(-0.66666667\)[/tex] and [tex]\(-2\)[/tex].
[tex]\[ x = \frac{-b \pm \sqrt{b^2 - 4ac}}{2a} \][/tex]
where [tex]\(a\)[/tex], [tex]\(b\)[/tex], and [tex]\(c\)[/tex] are the coefficients of the terms in the quadratic equation [tex]\(ax^2 + bx + c = 0\)[/tex]. For our specific equation [tex]\(3x^2 + 8x + 4 = 0\)[/tex], the coefficients are:
- [tex]\(a = 3\)[/tex]
- [tex]\(b = 8\)[/tex]
- [tex]\(c = 4\)[/tex]
Given the values of [tex]\(a\)[/tex], [tex]\(b\)[/tex], and [tex]\(c\)[/tex], we substitute them into the quadratic formula to solve for [tex]\(x\)[/tex]:
1. Compute the discriminant: [tex]\(b^2 - 4ac\)[/tex]
[tex]\[ b^2 - 4ac = 8^2 - 4 \cdot 3 \cdot 4 = 64 - 48 = 16 \][/tex]
2. Compute the two roots using the quadratic formula:
[tex]\[ x_1 = \frac{-b + \sqrt{b^2 - 4ac}}{2a} = \frac{-8 + \sqrt{16}}{2 \cdot 3} = \frac{-8 + 4}{6} = \frac{-4}{6} = -\frac{2}{3} \][/tex]
[tex]\[ x_2 = \frac{-b - \sqrt{b^2 - 4ac}}{2a} = \frac{-8 - \sqrt{16}}{2 \cdot 3} = \frac{-8 - 4}{6} = \frac{-12}{6} = -2 \][/tex]
These calculations yield the roots of the quadratic equation. Therefore, the solution set for the equation [tex]\(3x^2 + 8x + 4 = 0\)[/tex] is:
[tex]\[ \boxed{-\frac{2}{3}, -2} \][/tex]
In decimal form, these roots are approximately:
[tex]\[ \boxed{-0.66666667, -2} \][/tex]
Hence, the values which satisfy the given quadratic equation are [tex]\(-0.66666667\)[/tex] and [tex]\(-2\)[/tex].
We appreciate your time. Please come back anytime for the latest information and answers to your questions. Your visit means a lot to us. Don't hesitate to return for more reliable answers to any questions you may have. Thank you for trusting Westonci.ca. Don't forget to revisit us for more accurate and insightful answers.